Startup Supply Chain – Scalability through Artificial Intelligence : Opportunities and Challenges - Jokipii, Ella (My University, 2025)
Startups play a vital role in both the economy and society, yet their chances of success are relatively small. This makes the exploration of their survival and scalability an important area of academic discussion. Therefore, this thesis aims to contribute to the discussion by examining the key processes of supply chain management (SCM) within the context of a startup's scalability. The study focuses on modern SCM practices that have emerged due to digitalisation and advancements in artificial intelligence (AI), suggesting that AI serves as a significant driver for process optimisation and competitive advantage. For this reason, the study seeks to identify the factors that differentiate a startup from an established firm and why the adoption of AI in startups may present unique opportunities and challenges due to their distinct characteristics. The findings highlight that AI can help both established and emerging companies solve SCM challenges, as AI applications are widely utilised in various SCM processes to improve efficiency and decision-making. The research recognises that startups can address common SCM pain points in scaling their supply chains through the implementation of AI technologies in areas such as customer relationship management (CRM), demand forecasting, procurement, inventory management, and innovation. Additionally, the study identifies notable challenges for startups related to AI in SCM, including the lack of resources, complexity, and ethical concerns. All in all, the findings suggest that integrating AI technologies into supply chain processes can help startups compensate for their limited resources and support decision-making in their uncertain and dynamic business environments. However, due to the associated risks, startups shouldn’t blindly trust AI. Understanding these opportunities and challenges can be seen as essential for supporting startups' survival and growth.

Startup-yritykset ovat elintärkeitä organisaatioita sekä taloudelle että yhteiskunnille. Niiden selviytymiseen ja skaalautumiskykyyn liittyen on kuitenkin tärkeää herättää lisää akateemista keskustelua, sillä todennäköisyys startupin menestymiselle on pieni. Tämä opinnäytetyö osallistuu keskusteluun tarkastelemalla toimitusketjujen hallinnan keskeisimpiä prosesseja startup-yrityksen skaalautuvuuden näkökulmasta. Tutkimus syventyy digitalisaation ja tekoälyteknologioiden myötä syntyneeseen moderniin toimitusketjujen hallintaan, jossa tekoäly nähdään merkittävänä ajurina prosessien tehostamisessa sekä yrityksen kilpailuedun saavuttamisessa. Tämän vuoksi tutkimus pyrkii selvittämään, mitkä tekijät erottavat startup-yrityksen vakiintuneesta yrityksestä ja miksi tekoälyn käyttöönotto startupissa voi piirteistään johtuen kohdata uniikkeja mahdollisuuksia ja haasteita. Tulokset korostavat, että tekoäly voi auttaa sekä vakiintuneita yrityksiä että startupeja ratkaisemaan toimitusketjujen hallintaan liittyviä haasteita, sillä tekoälysovelluksia hyödynnetään laajasti erilaisissa toimitusketjujen hallinnan prosesseissa tehokkuuden ja päätöksenteon parantamiseksi. Startup-yritys voi ohittaa monia tavallisia kipukohtia toimitusketjunsa skaalaamisessa hyödyntämällä tekoälyteknologiaa muun muassa asiakassuhteiden hallinnassa, kysynnän ennustamisessa, hankinnassa, varastonhallinnassa ja innovoinnissa. Tutkimus tunnistaa myös merkittäviä haasteita tekoälyn hyödyntämisessä toimitusketjujen hallinnan tukena, joista keskeisimpinä voidaan nähdä resurssien puute, monimutkaisuus ja eettiset riskit. Tutkimuksen perusteella voidaan todeta, että tekoälyteknologioiden käyttäminen startupin toimitusketjun prosesseissa voi auttaa startupeja kompensoimaan rajallisia resurssejaan sekä tukea päätöksentekoa startupille luonteenomaisessa epävarmassa ja muuttuvassa liiketoimintaympäristössä. Tunnistettujen haasteiden vuoksi startup-yritysten ei kuitenkaan tulisi luottaa sokeasti siihen, mitä tekoäly mahdollistaa. Näiden mahdollisuuksien ja haasteiden tunnistaminen voi tukea startupin selviytymistä ja kasvua.
Keywords: artificial intelligence, scalability, supply chain management, startup